CD4-binding site alterations in CCR5-using HIV-1 envelopes influencing gp120-CD4 interactions and fusogenicity - Sterjovski, J.; Churchill, M.; Roche, M.; Ellett, A.; Farrugia, W.; Wesselingh, S.; Cunningham, A.; Ramsland, Paul; Gorry, P. (2011)
CD4-binding site (CD4bs) alterations in gp120 contribute to different pathophysiological phenotypes of CCR5-using (R5) HIV-1 strains, but the potential structural basis is unknown. Here, we characterized functionally diverse R5 envelope (Env) clones (n = 16) to elucidate potential structural alterations within the gp120 CD4bs that influence Env function. Initially, we showed that the magnitude of gp120-CD4-binding correlates with increased fusogenicity and reduced CD4 dependence. Analysis of three-dimensional gp120 structural models revealed two CD4bs variants, D279 and N362, that were associated with reduced CD4 dependence. Further structural analysis showed that a wider aperture of the predicted CD4bs cavity, as constrained by the inner-most atoms at the gp120 V1V2 stem and the V5 loop, was associated with amino acid alterations within V5 and correlated with increased gp120-CD4 binding and increased fusogenicity. Our results provide evidence that the gp120 V5 loop may alter CD4bs conformation and contribute to increased gp120-CD4 interactions and Env fusogenicity.